Evolução tecnológica de sistemas Fotovoltaicos ao longo dos tempos: Estudo de caso de uma propriedade rural no munícipio de Cascavel/PR. - Lazzarin, Rafaela (2023)
Technological developments in the photovoltaic area have played a fundamental role in achieving the primary objective, which is to increase the efficiency of converting sunlight into electrical energy. Advances in solar cell technology, photovoltaic modules, inverters and other equipment used are improving the performance of photovoltaic systems, and have led this technology to establish itself as a strongly competitive energy source. Therefore, this work examines the evolution of photovoltaic materials over time, through a literature review, showing significant cost reductions, as well as the evolution of increased efficiency, attributed to technological innovation and improvements in manufacturing. Subsequently, two photovoltaic systems (on-grid and off-grid) were designed for a residence in the rural area of the municipality of Cascavel - PR with an average monthly consumption of 489 kWh, simulating the use of equipment currently used. After the sizing, economic indices were calculated such as: NPV (Net Present Value), PBD (Discounted Payback) and LCOE (Levelized cost of energy), indicating the unit cost of energy generated between the systems. The total price of the on-grid system was 27095.50 with a payback period of 7 years and the LCOE of 23426.00, showing the economic viability of the system. The off-grid system had a total price of 65273.00, there was no payback time within 25 years, and the NPV had a negative value, therefore, the system did not show economic viability. Comparisons of economic viability, prices, efficiencies were made between photovoltaic equipment used in the 1990s with equipment currently used. The results found show that the value of the LCOE for the 1990s was around US$ 0.60/kWh. The LCOE values found for the sizing were: US$0.353/kWh (off-grid) and US$0.0758 (on grid). Based on the presented bibliography, the LCOE projection for 2050 is from 0.030/kWh to US$ 0.010/kWh.